Unilateral inguinal lymphadenopathy in a 6-year-old girl: An unusual presentation of Rosai-Dorfman disease - Rakesh Kumar Pilania; Aman Gupta; Zaidi Ariba; Pandiarajan Vignesh (Elsevier, 2019)
Rosai Dorfman disease (RDD) commonly presents as bilateral cervical lymphadenopathy in children and young adults. We herein report a young girl with unilateral inguinal lymphadenopathy as a rare presentation of RDD. Keywords: Child, Rosai Dorfman disease, Unilateral lymphadenopathy